2020
DOI: 10.1002/cbic.202000298
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Apo‐Form Selective Inhibition of Indoleamine 2,3‐Dioxygenase**

Abstract: Indoleamine‐2,3‐dioxygenase 1 (IDO1) is a heme‐containing enzyme that catalyzes the rate‐limiting step in the kynurenine pathway of tryptophan (TRP) metabolism. As it is an inflammation‐induced immunoregulatory enzyme, pharmacological inhibition of IDO1 activity is currently being pursued as a potential therapeutic tool for the treatment of cancer and other disease states. As such, a detailed understanding of the mechanism of action of IDO1 inhibitors with various mechanisms of inhibition is of great interest.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…While apo inhibitors show a lack of inhibition in the enzyme‐based assay in face of a high cellular activity, [18,19,45] VS9 provided an rhIDO1 inhibition of 54.6±3.1 % (see also Supporting Information), comparable to the result from the cellular‐based assay. To further confirm the absence of binding to the apo‐form, the interference of the compound with the amount of free heme produced after incubation with IDO1 was evaluated [19] . Similarly to epacadostat, VS9 did not increase the levels of free heme (see Supporting Information), confirming the molecule as a catalytic holo‐inhibitor.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…While apo inhibitors show a lack of inhibition in the enzyme‐based assay in face of a high cellular activity, [18,19,45] VS9 provided an rhIDO1 inhibition of 54.6±3.1 % (see also Supporting Information), comparable to the result from the cellular‐based assay. To further confirm the absence of binding to the apo‐form, the interference of the compound with the amount of free heme produced after incubation with IDO1 was evaluated [19] . Similarly to epacadostat, VS9 did not increase the levels of free heme (see Supporting Information), confirming the molecule as a catalytic holo‐inhibitor.…”
Section: Resultsmentioning
confidence: 55%
“…rhIDO1 was treated with 10 μM of VS9 and the conversion of L-Trp to L-Kyn was determined spectrophotometrically using p-dimethylaminobenzaldehyde. While apo inhibitors show a lack of inhibition in the enzymebased assay in face of a high cellular activity, [18,19,45] VS9 provided an rhIDO1 inhibition of 54.6 � 3.1 % (see also Supporting Information), comparable to the result from the cellularbased assay. To further confirm the absence of binding to the apo-form, the interference of the compound with the amount of free heme produced after incubation with IDO1 was evaluated.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Röhrig et al., [67] Ortiz‐Moez et al., [68] and others [69] described Linrodostat as an apo‐form IDO1 inhibitor standing for the kinetic study results and spectroscopic determinations [67–68] . Moreover, Ortiz‐Moez's study [68] raised the concern of the physiological conditions that support the existence of IDO1 in apo‐form more than the holo‐form, to justify obtaining results agree with Nelp et al. study [35] and disagrees with the Pham et al.…”
Section: Discovery Of the Clinical Candidates Of Selective Hido1 Inhibitors And The Scheme Of Binding Inhibition Into The Enzyme Active Smentioning
confidence: 95%
“…However, a number of clinical trials were terminated due to the lack of reported benefits [150], thus suggesting the need to establish a novel strategy to block L-Trp catabolism. Interestingly, a novel inhibitor of IDO1 that blocks the binding of the haem-free conformation of the enzyme (apo-IDO1) has been identified (GSK5628) and was recently synthesised [151]. In comparison to traditional drugs that bind to the iron atom of the IDO1 heme cofactor (holo-IDO1), this compound guarantees a durable inhibitory effect.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%